2021
DOI: 10.37723/jumdc.v12i2.535
|View full text |Cite
|
Sign up to set email alerts
|

Pallidotomy in Parkinsonian Disease: The Renaissance

Abstract: ABSTRACT: BACKGROUND & OBJECTIVE: To assess the results of pallidotomy in Parkinson’s disease, and its effect on improving the lifestyle of the patients and cost-effectiveness. METHODOLOGY: A descriptive study was conducted at Neuro-Spinal & Cancer Care Institute, Karachi from June 2014 to January 2020. Patients who were known case of Parkinson’s disease refractory to medication and developed side effects to medication were included in the study and patients with previous brain surgery, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Subsequent investigations have shown that bilateral thalamotomy, specifically, has a higher level of risk compared to DBS targeting the thalamus. Similarly, the medical procedure known as pallidotomy, first proposed by Kalhoro, Sattar, Hashim, and Saleem [3] as a potential PD treatment that proved to be resistant to conventional medical interventions during the early 1990s, has been shown to possess a lower level of safety compared to globus pallidus stimulation. The DBS has been widely regarded as a safe therapy in these locations, leading to a progressive decline in the usage of lesional operations.…”
Section: Present and Future Of Deep Brain Stimulationmentioning
confidence: 99%
“…Subsequent investigations have shown that bilateral thalamotomy, specifically, has a higher level of risk compared to DBS targeting the thalamus. Similarly, the medical procedure known as pallidotomy, first proposed by Kalhoro, Sattar, Hashim, and Saleem [3] as a potential PD treatment that proved to be resistant to conventional medical interventions during the early 1990s, has been shown to possess a lower level of safety compared to globus pallidus stimulation. The DBS has been widely regarded as a safe therapy in these locations, leading to a progressive decline in the usage of lesional operations.…”
Section: Present and Future Of Deep Brain Stimulationmentioning
confidence: 99%